Assessment of Pathogenic Potential of Two Indian H5N1 Highly Pathogenic Avian Influenza Virus Isolates by Intravenous Pathogenicity Index Test - Shankar, B.P.; Gowda, R.N.S.; Prabhu, B. H. Manjunath; Pattnaik, B.; Nagarajan, S.; Patil, S.S.; Pradhan, H.K. (International Journal of Poultry Science, 2009)
Intravenous Pathogenicity Index (IVPI) test was conducted to assess the pathogenicity of two H5N1 (A/Ck/Ind/7966/06 and A/Ck/Ind/7972/06) AIV isolates. Both the H5N1 virus isolates were isolated from natural outbreaks during 2006, both isolates caused death of all birds with in 48 h after inoculation experimentally, birds showed typical clinical signs, gross and microscopic lesions of Avian influenza. IVPI of A/Ck/Ind/7966/06 and A/Ck/Ind/7972/06 was 2.96 and 2.95 respectively. This test showed that both H5N1 isolates are highly pathogenic. Virus could be re-isolated from all the organs of infected chickens and it was reconfirmed by RT-PCR using WHO and Lee primers.